Grid integration of wind energy - Heier, Siegfried; Wiley eBooks (Chichester, West Sussex, United Kindgom : John Wiley & Sons Inc., 2014)
"This timely update provides detailed treatment of the integration of wind power into electrical power systems, including brand new material on offshore wind power farms and technologiesThis third English edition is based on new material from the fourth and fifth German editions (Windkraftanlagen: Systemauslegung, Netzintegration und Regelung, 5. Auflage, published by Teubner B.G. Gmbh, July 2009). It answers the question of how, with the proper control and direction, wind turbines can be made to operate more similarly to conventional power plants. The revised third edition addresses the engineering challenges of cost effective transmission and distribution of wind power, such as technical, economic and safety issues. It also incorporates all the recent technical developments in electrical power conversion systems and essential operating conditions, and includes unique, original research findings carried out by the author's own PhD and Masters students at Kassel University, Germany. This popular reference book has been updated to include new material from the fourth and fifth German editions, equating to 12.5% brand new material New material covers the 'hot topic' of grid connection for offshore wind farms and offshore technologies, including lots of illustrations Brand new material on low voltage fault dynamics and control of turbines Includes up-to-date coverage on completely new generator developments for wind turbines, developed over the past two years Illustrates how wind turbines can operate like conventional power plants using advanced control systems. Discusses the profitability of wind turbine integration in electrical power grids, and the environmental impact "--
"New material covers the 'hot topic' of grid connection for offshore wind farms and offshore technologies, including lots of illustrations"--
Translation of: Windkraftanlagen im Netzbetrieb.
Includes bibliographical references and index.
Translated from the German.
John Wiley and Sons
Keywords: Wind power plants; Wind energy conversion systems; Electric power systems; TECHNOLOGY & ENGINEERING -- Power Resources -- General; Electric power systems; Wind energy conversion systems; Wind power plants; Electronic books